السياسة النقدية بين المرونة ومنهج القواعد في ميزان الاقتصاد الإسلامي - عبد الرزاق, . نذير; الطيب, داودي (Recherches économiques et managériales; Vol. 15 (2014): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2014)
تعتبر السياسة النقدية إحدى السياسات الاقتصادية التي تعمل على تحقيق الاستقرار الاقتصادي، وتختص السياسة النقدية بمراقبة سلوك النقود في الاقتصاد وتصحيحه وتوجيهه نحو الوجهة السليمة، وتتفق جميع المدارس بتعريف السياسة النقدية لكن الاختلاف يكمن في نقطتين هامتين الأولى هي ماهية الأهداف التي تحاول السياسة النقدية تحقيقها والثانية كيفية عمل السياسة النقدية. Abstract     Considers monetary policy  One the economic policies  working to achieve economic stability، monetary policy control  the behavior of money in the economy and corrective and directed towards the right direction، consistent all schools definition of monetary policy but the difference lies in two important points: The first is the nature of the goals that are trying to monetary policy achieved and second how the monetary policy work، and aims article to clarify the most important developments in the work of politics monetary and choose the nearest approaches to Islamic Economics.